ENHANCING AUDIENCE AWARENESS OF CHINESE SECOND LANGUAGE WRITERS IN SINO-US WRITING PROGRAMME - Liang, Jingbi (PEOPLE: International Journal of Social Sciences, 2015)
This paper aims to explore in the second language writing how Chinese university students enhance their audience awareness linguistically and culturally in web-based Sino-US peer-editing programmed Cross-Pacific Exchange with Pennsylvania State University. The programmed has lasted 6 years since 2009. This research will be focused on the two-week project about review writing on two films —Blind Mountain (1997 in China) and Nightmare (1976 in America), which are related to gender and social issues (woman trafficking, drowning of new-born baby girls, racism between white and black people, illegal use of prisoners as slaves and etc.) Twenty-three pairs of Chinese-American students conducted peer-editing, kept close contact on our Program website. Descriptive methodology is adopted—analysis of students’ works (including the first draft, revised drafts, peer-editing and reflection). Under Hyland’s Stance and Engagement Model, the study suggests that through contact with native target readers, the audience awareness of Chinese students has been greatly raised both at linguistic and cultural levels to achieve shared knowledge, like avoiding the meaning tangled by using unnecessary formal complicated words, more aware of the semantic prosody, appropriate use of thesis statement and topic sentences; and trying to understand other’s culture as well as appropriately to deliver their own cultural value.